East Asia Pacific at Work : Employment, Enterprise, and Well-being - Packard, Truman G. (Washington, DC: World Bank, 2014)
The unprecedented progress of East Asia Pacific is a triumph of working people. Countries that were low-income a generation ago successfully integrated into the global value chain, exploiting their labor-cost advantage. In 1990, the region held about a third of the world’s labor force. Leveraging this comparative advantage, the share of global GDP of emerging economies in East Asia Pacific grew from 7 percent in 1992 to 17 percent in 2011. Yet, the region now finds itself at a critical juncture. Work and its contribution to growth and well-being can no longer be taken for granted. The challenges range from high youth inactivity and rising inequality to binding skills shortages.